2015
DOI: 10.1149/2.0231602jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Stack Testing of Solid Oxide Fuel Cells with Cathodes Prepared by Infiltration

Abstract: Large footprint (144 cm 2 ) cells with infiltrated (La 0.6 Sr 0.4 ) 0.95 FeO 3 /yttria-stabilized zirconia (LSF-YSZ) cathodes were fabricated on a pre-production scale (approximately 90 cells/batch). The excellent electrochemical performance of the cells was confirmed both on single cell as well as on stack level. Changes in electrode properties were mapped out as a function of heat-treatment temperature. The microstructure of the porous zirconia backbone remained unchanged, but the surface area of the ferrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…[189] They did multiple impregnation steps and followed the amount of added material, and then looked at both the microstructure and in-plane electrode resistance, to correlate with cell performance. They used standard cell impregnation methods to improve cathodes.…”
Section: Scaleup and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…[189] They did multiple impregnation steps and followed the amount of added material, and then looked at both the microstructure and in-plane electrode resistance, to correlate with cell performance. They used standard cell impregnation methods to improve cathodes.…”
Section: Scaleup and Outlookmentioning
confidence: 99%
“…Topsoe fuel cells have looked at impregnation on the stack level to help the performance and durability of its stacks. They used standard cell impregnation methods to improve cathodes . They did multiple impregnation steps and followed the amount of added material, and then looked at both the microstructure and in‐plane electrode resistance, to correlate with cell performance.…”
Section: Scaleup and Outlookmentioning
confidence: 99%
“…Degradation in infiltrated electrodes is commonly attributed to nano-particle coarsening. 18,19,24,34,54,[56][57][58] Numerous independent studies have shown that electrocatalyst particle size (and hence the electrochemically active surface area) plays a major role in determining the performance of infiltrated electrodes. In one such study, the performance of an infiltrated La 0.8 Sr 0.2 FeO 3 electrode, deactivated by heattreatment, could be restored to close to original performance by a single infiltration of fresh La 0.8 Sr 0.2 FeO 3 , and the extent of re-activation could be predicted from the associated electrode BET surface area increase.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the cathode backbone concept is that of number of sintering steps in manufacturing process of the SOFCs is reduced. 34 Here only one sintering process at high temperatures is necessary; the heat-treatment steps that follow the infiltration process are performed at much lower temperature (≤400 • C) (Figure . 1b).…”
mentioning
confidence: 99%
“…21,22 Figure 1 shows two representative images of conventional and infiltrated architectures a . While the latter architecture guarantees a large density of reaction sites, thus decreasing the electrode polarization resistance, [23][24][25] the durability over extended operation [26][27][28] and redox cycling 29,30 requires additional optimization, 31,32 especially for infiltrated Ni in the anode.…”
Section: List Of Symbolsmentioning
confidence: 99%